Internalisasi Nilai-Nilai Dakwah dalam Bauran Pemasaran Pendidikan - Chasannudin, Arif (Mu'ashir: Jurnal Dakwah dan Komunikasi Islam, 2025)
This article aims to develop a conceptual framework that integrates Islamic da‘wah values into educational service marketing practices, which have long tended to be commercially oriented. Educational marketing strategies generally refer to the 7Ps of the marketing mix: product, price, place, promotion, people, process, and physical evidence yet their implementation remains dominated by business-oriented perspectives, resulting in limited integration of Islamic ethical and spiritual values. This study employs a qualitative approach through a literature review of research on educational marketing and da‘wah values. Relevant journal articles were identified using the Publish or Perish application linked to Google Scholar. The search was conducted in September 2025 using the keywords “pemasaran, siddiq, tabligh, amanah, fathanah,” with publications restricted to the years 2020–2025. The literature review reveals a strong need to integrate Islamic da‘wah values: siddiq, amanah, tabligh, fathanah, syaja’ah, and uswatun hasanah into educational marketing strategies. These values serve as essential ethical and spiritual foundations for the human resources involved in marketing activities. The internalization of da‘wah values in educational marketing encourages a shift from purely commercial orientations toward a more humanistic, ethical, and spiritually grounded approach. This integration aligns marketing practices with the exemplary character of Prophet Muhammad (peace be upon him), thereby strengthening integrity and trust within educational institutions.